"Evaluation of Environmental News Coverage in Print Media of Bangladesh" - Ferdousy, Shabnam (The Jahangirnagar Review Part-C, 2024)
This study assesses the coverage of environmental news in print media of Bangladesh. Here four newspapers in two languages are taken as a sample to evaluate the coverage of environmental news which are The Daily Prothom Alo, The Daily Ittefaq. The Daily Star and The Business Standard. Here, 124(314) newspapers are taken from 01 January 2023 to 31 January 2023. Analyzing these, a total of 9002 news items were found, of which 187 were environmental news items which is very insignificant compared to the total news. Here the news topics include pollution, biodiversity, environmental management, brick kilns, illegal sand mining, hill cutting. deforestation and environmental threats. Out of which most of the news has been published on pollution and biodiversity. Most of these stories are published in a strait jacket news format and in two columns. As environment has become an important issue today. Concerns about the environment are growing and therefore the coverage of environmental news is increasing globally. But this study shows that environmental news has not become so important in the newspapers of Bangladesh. This result also indicates that official voice extremely reliant as source of environmental news. While environment specialist, scientists were all but ignored as news sources. Numbers of in-depth news also very poor. They were given very small treatment. Here the newspapers have published the same type of news in determining the agenda of the news. Each newspaper followed its own framing method in the content and structure of its news.